Electromobility: An Analysis of Public Policies for Sustainable Public Transport in Curitiba - Torres, Ricardo Lobato; Paixão , Natália Caldas Reis da (Technical and Scientific Journal Green Cities, 2025)
ABSTRACT Objective – This study analyzes electromobility in Curitiba, evaluating the progress of sustainable public transport and existing public policies, as well as the capacity to serve Brazil’s eighth most populous city. The research aims to understand how these policies contribute to the decarbonization of public transport and the mitigation of urban environmental impacts. Methodology – The study conducted a documentary evaluation of municipal mobility and electromobility plans and guidelines, including the Curitiba Urban Master Plan (2015), the National Urban Mobility Policy (Law 12.587/12), the Climate Action Plan (PlanClima), and Curitiba’s Sustainable Urban Mobility Program. Originality/relevance – This study fills a gap by critically analyzing the implementation of electromobility in Curitiba within the context of sustainable public transport policies. The research highlights public authorities’ concern with sustainability and the efficiency of modal integration in the city. Results – The findings indicate that Curitiba has advanced in implementing electromobility policies, promoting environmental and economic benefits. The adoption of electric buses and incentives for sustainable mobility demonstrate a commitment to reducing emissions and improving air quality while fostering a more efficient transportation system. Theoretical/methodological contributions – The research contributes to the debate on electromobility in Brazil by offering a detailed documentary analysis of current public policies. Additionally, it proposes guidelines to optimize the governance of sustainable urban mobility. Social and environmental contributions – The transition to electromobility directly impacts urban quality of life by reducing pollution and promoting public health benefits. The study reinforces the importance of government initiatives to consolidate more sustainable and accessible public transport systems.